Strategi pembangunan Kawasan Ekonomi Khusus (KEK) Sulawesi Tenggara: Kajian potensi daerah berbasis sektor unggulan - Halik, Faturrohman Muhammad (Journal of Economics Research and Policy Studies, 2025)
The development of regional economic potential plays a strategic role in supporting national growth, particularly through Kawasan Ekonomi Khusus (KEK). Southeast Sulawesi, as part of the Sulawesi Economic Corridor under Indonesia’s Masterplan for Acceleration and Expansion of Economic Development (MP3EI), has been designated as a "Center for the Production and Processing of Agricultural, Plantation, Fishery, and Nickel Mining Products". This study aims to evaluate the alignment between the KEK theme and Southeast Sulawesi’s regional economic potential using the Location Quotient (LQ), Dynamic Location Quotient (DLQ), Shift-Share Analysis, and Klassen Typology methods. The results reveal two key sectors: the fishery subsector and the basic metal industry subsector. The fishery subsector is supported by abundant marine resources and high-export commodities such as frozen octopus, seaweed, and pelagic fish. Meanwhile, the basic metal industry is driven by the region’s vast nickel reserves, producing ferronickel and stainless steel for export. This study concludes that the KEK development aligns well with the region’s potential.